2020
DOI: 10.1017/s1355617720000545
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Functional Relation Between Set Shifting and Hyperactivity in Children with Attention-Deficit/Hyperactivity Disorder (ADHD)?

Abstract: Objective: Replicated evidence indicates that children with attention-deficit/hyperactivity disorder (ADHD) show disproportionate increases in hyperactivity/physical movement when their underdeveloped executive functions are taxed. However, our understanding of hyperactivity’s relation with set shifting is limited, which is surprising given set shifting’s importance as the third core executive function alongside working memory and inhibition. The aim of this study was to experimentally examine the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In addition to replicated evidence of CET’s direct benefits for children with ADHD, the present findings also have implications for conceptual models of academic functioning by providing causal evidence that improving working memory results in improvements in overall academic achievement, math and reading skills specifically, and academic productivity and success in the classroom. Additional research is needed to examine the extent to which CET-related improvements in working memory also portend improvements in other functional domains (e.g., peer/social and family functioning, organizational skills, activities of daily living; Abikoff et al, 2013; Irwin et al, 2021; Mikami & Normand, 2015) and cognitive functions (e.g., set shifting; Irwin et al, 2019, 2020) that are impaired in children with ADHD and linked with their working memory difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to replicated evidence of CET’s direct benefits for children with ADHD, the present findings also have implications for conceptual models of academic functioning by providing causal evidence that improving working memory results in improvements in overall academic achievement, math and reading skills specifically, and academic productivity and success in the classroom. Additional research is needed to examine the extent to which CET-related improvements in working memory also portend improvements in other functional domains (e.g., peer/social and family functioning, organizational skills, activities of daily living; Abikoff et al, 2013; Irwin et al, 2021; Mikami & Normand, 2015) and cognitive functions (e.g., set shifting; Irwin et al, 2019, 2020) that are impaired in children with ADHD and linked with their working memory difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to replicated evidence of CET's direct benefits for children with ADHD, the current findings also have implications for conceptual models of academic functioning by providing causal evidence that improving working memory results in improvements in overall academic achievement, math and reading skills specifically, and academic productivity and success in the classroom. Additional research is needed to examine the extent to which CET-related improvements in working memory also portend improvements in other functional domains (e.g., peer/social and family functioning, organizational skills, activities of daily living; Abikoff et al, 2013;Irwin et al, 2021;Kofler et al, 2017;Mikami & Normand, 2015) and cognitive functions (e.g., set shifting; Irwin et al, 2019Irwin et al, , 2020 that are impaired in children with ADHD and linked with their working memory difficulties. Achievement; GSV = standardized growth scale values (for all subtests, the average GSV for grade 3 is anchored at 500.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…The cognitive tests used during actigraphy in this study required participants to interact with investigators and respond to questions in a one-on-one structured session; these conditions could have the effect of stymieing hyperactivity [33]. Previous actigraph studies have indicated that ADHD-related hyperactivity is modulated by situational demands on executive functioning, with more intensive situations eliciting more hyperactivity [55][56][57]. It is unclear if this same pattern holds true for individuals with TSC or other disorders who may have significant cognitive issues due to ADHD as well as other psychological and neurological issues.…”
Section: Discussionmentioning
confidence: 99%